2016
DOI: 10.1016/j.biortech.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Marine microalgae growth and carbon partitioning as a function of nutrient availability

Abstract: To understand in which way the structural differences of three marine microalgae (Nannochloropsis gaditana, Rhodomonas marina and Isochrysis sp.) affect their carbon partitioning, growth and applicability; a stoichiometric imbalance was imposed by steady carbon and other nutrients variation. Towards high nutrients concentrations/low carbon availability a decrease of 12-51% in C/N microalgae ratio was observed and maximum cell densities were achieved. Moreover, linear correlation between the nutrient input and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
1
23
1
1
Order By: Relevance
“…Carbon and phosphorus from phytoplankton were assimilated more efficiently than bacteria, even high C : P phytoplankton that had an extreme C : P ratio of 2115 : 1 AE 555. T. lutea has a flexible stoichiometry, when grown under nutrient-limited conditions, cell protein content decreased markedly and lipid content more than doubled (Fernandes et al 2016) and phytoplankton C : P stoichiometries similar to our experiments have been recorded in natural assemblages in freshwaters . Under high C : P conditions phytoplankton can develop grazing-resistant strategies, such as mucilage, or thicker cell walls, enabling passage through the gut without digestion (Van Donk et al 1997;Reynolds 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Carbon and phosphorus from phytoplankton were assimilated more efficiently than bacteria, even high C : P phytoplankton that had an extreme C : P ratio of 2115 : 1 AE 555. T. lutea has a flexible stoichiometry, when grown under nutrient-limited conditions, cell protein content decreased markedly and lipid content more than doubled (Fernandes et al 2016) and phytoplankton C : P stoichiometries similar to our experiments have been recorded in natural assemblages in freshwaters . Under high C : P conditions phytoplankton can develop grazing-resistant strategies, such as mucilage, or thicker cell walls, enabling passage through the gut without digestion (Van Donk et al 1997;Reynolds 2007).…”
Section: Discussionsupporting
confidence: 89%
“…This confirmed that an excess of nitrogen supply does not lead to growth inhibition. However, our results show that C. vulgaris needs more nitrogen input than other microalgal species such as Nannochloropsis, Rhodomonas, Isochrysis or Choricystis to render the maximum biomass productivity [56,57]. Notwithstanding, we consider that this characteristic must be considered when using this microalga in wastewater treatments [58][59][60].…”
Section: Discussionmentioning
confidence: 85%
“…N. gaditana has been documented to grow well in both indoor and outdoor conditions and has been studied for the optimization of lipid accumulation and pigment production. Under nitrogen starvation conditions, N. gaditana is known to accumulate lipids in the order of 40-60% (w/w) (Fabregas et al, 2002;Rocha et al, 2003;Benito et al, 2015;Fernandes et al, 2016) in the form of triacylglycerol and polyunsaturated fatty acids (PUFA) (Ma et al, 2016). The current market-relevant production of Nannochloropsis strains is mainly as food supplements for Eicosapentaenoic Acid (EPA), as aquaculture feed in the form of concentrates and pastes, and in skin care products (Enzing et al, 2014;Riveros et al, 2018).…”
Section: Introductionmentioning
confidence: 99%